2014
DOI: 10.1155/2014/503920
|View full text |Cite
|
Sign up to set email alerts
|

Chaotic Analysis of the Electroretinographic Signal for Diagnosis

Abstract: Electroretinogram (ERG) is a time-varying potential which arises from different layers of retina. To be specific, all the physiological signals may contain some useful information which is not visible to our naked eye. However this subtle information is difficult to monitor directly. Therefore the ERG signal features which are extracted and analyzed using computers are highly useful for diagnosis. This work discusses the chaotic aspect of the ERG signal for the controls, congenital stationary night blindness (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 23 publications
0
4
0
1
Order By: Relevance
“…Although linear methods are mostly used in analyzing ERG signals, nonlinear features also show aspects that cannot be investigated using linear methods. However, published works in this field are still deficient [109][110][111][112][113]. Using nonlinear tools to represent chaotic behaviors can be a good choice for discovering the ERG signal's nature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although linear methods are mostly used in analyzing ERG signals, nonlinear features also show aspects that cannot be investigated using linear methods. However, published works in this field are still deficient [109][110][111][112][113]. Using nonlinear tools to represent chaotic behaviors can be a good choice for discovering the ERG signal's nature.…”
Section: Discussionmentioning
confidence: 99%
“…Molaie et al [113] worked on flash frequency and contrast as effective parameters in the ERG recordings. They reported that these parameters significantly impact the recorded signals and lead to bifurcations, indicating chaotic behavior.…”
Section: F Nonlinear Methodsmentioning
confidence: 99%
“…These features include the Lyapunov exponent, Hurst exponent, approximate entropy, and fractal dimension. Nonlinear features have made a good distinction between healthy and abnormal groups [27]. Another feature that could show the dynamic of ERG in CRVO patients was mapping the ERG to a parabolic curve and extracting an angle criterion based on the arrangement of points on a new curve [28].…”
Section: Discussionmentioning
confidence: 99%
“…Different signal processing methods have been applied to ERG, including timedomain, frequency-domain, and time-frequency domain analyses [20][21][22][23][24][25][26]. Besides, nonlinear features have been used to analyze the ERG [27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Rod yanıtı karanlık adaptasyon sonrasında fERG ölçümlerinde elde edilen ilk sinyaldir. Kon yanıtı aydınlık adaptasyon sonrası kon hücrelerinden, maksimum kombine yanıtı ise karanlık adaptasyon sonrası hem rod hem de kon hücrelerinden elde edilen yanıtlardır [12].…”
Section: Introductionunclassified